Pengaruh Konsentrasi Doping TiO₂ dan Volume Diethanolamine (DEA) terhadap Nilai Bandgap CuO dengan Metode Sol-Gel - Sakina Cahaya Fatma; Hary Sanjaya; Miftah Patriela (Lembaga Yasin AlSys, 2025)
Copper(II) oxide (CuO) is a promising semiconductor material for various applications such as photocatalysis, sensing, and renewable energy devices. However, its performance is often limited by a suboptimal bandgap value for efficient energy conversion. This study aims to evaluate the effects of titanium doping concentration and the addition volume of diethanolamine (DEA) on the optical properties of CuO synthesized via the sol-gel method. The sol-gel technique was chosen for its ability to produce uniform doping distribution and stable nanoparticle structures. Bandgap characterization was conducted using UV-DRS spectroscopy. The results show that the bandgap of pure CuO, initially measured at 1.36 eV, was reduced to 1.28 eV through titanium doping at an optimal concentration of 0.3 mmol. The further addition of DEA at an optimal volume of 1 mL lowered the bandgap to 1.22 eV. This reduction indicates that titanium doping and DEA addition significantly influence the optical properties of CuO. These effects are likely due to structural irregularities such as oxygen vacancies, crystal defects, and impurities, which contribute to modifications in the material’s electronic structure. Additionally, the uniform distribution of microstrain and smaller particle size further contribute to structural alterations and bandgap tuning.